2015
DOI: 10.1089/mdr.2014.0172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Carbapenem Resistance in Multidrug-Resistant Clinical Isolates ofPseudomonas aeruginosafrom a Croatian Hospital

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen, one of the leading causes of nosocomial infections such as pneumonia, urinary tract infections, and bacteraemia. The bacterial resistance to structurally unrelated antibiotics and its spread within hospitals limits the efficient antimicrobial options and patients' outcome. Carbapenems are important agents for the therapy of infections due to multidrug-resistant (MDR) P. aeruginosa; hence, the development of carbapenem resistance severely hampers effective th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Both species showed resistance to cephalosporins. Previous studies from Canada, Croatia, and Latin America found P. aeruginosa isolates resistant to carbapenems, aminoglycosides, and ciprofloxacin but not to piperacillin [14, 15]. Citrobacter isolates showed resistance to eight antibiotics whereas they were moderately susceptible to other antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Both species showed resistance to cephalosporins. Previous studies from Canada, Croatia, and Latin America found P. aeruginosa isolates resistant to carbapenems, aminoglycosides, and ciprofloxacin but not to piperacillin [14, 15]. Citrobacter isolates showed resistance to eight antibiotics whereas they were moderately susceptible to other antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, the frequency of antimicrobial resistance has increased globally. MDR bacteria are now recognized as a major cause of nosocomial infections, representing a serious safety concern for both health care practitioners and the patients [9,14]. The risk of MDR bacterial infection has been related to a number of factors, including long-term antimicrobial therapy, cross-transmission, length of hospital stay, and invasive procedures [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Common bacteria that show MDR/PDR are methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing bacteria, carbapenem-resistant Enterobacteriaceae (CRE), carbapenem-resistant Acinetobacter baumannii (A. baumannii, CRAB), MDR/PDR Pseudomonas aeruginosa (P. aeruginosa, MDR/PDRPA), and MDR Mycobacterium tuberculosis [6][7][8]. A high prevalence of nosocomial infections attributable to MDR strains has been reported in countries worldwide [8][9][10][11][12]. In 2014, the average MRSA detection rate across 17 Chinese hospitals was 44.6% (29.1% to 74.2%), and the detection rates of ESBL-producing Escherichia coli (E. coli, ESBLECO) and ESBL-producing Klebsiella pneumoniae (ESBLKPN) were 55.8% and 29.9%, respectively [10].…”
Section: Introductionmentioning
confidence: 99%
“…␤-lactams (4,5). The chromosomally encoded broad-spectrum AmpC ␤-lactamase contributes to the natural resistance of P. aeruginosa to many ␤-lactam antibiotics together with MexAB-OprM (6).…”
mentioning
confidence: 99%